Effectiveness of Smart Home System Technology on Property - Praymoedya Alramadhan Bahroun; Kurnia Tsani Alamsyah; Khaira Ummah; Herry Saputra; Hanhan Maulana (Universitas Komputer Indonesia, 2021)
The purpose of this study is to find out how effective the use of smart home system technology is on properties; smart home systems can make it easier for users to control functions automatically. The research method used is a qualitative method in order to find out in depth how effective the use of the smart home system technology is. Along with the development of the times, technology also accompanies the property in terms of security, comfort, convenience, and cleanliness. Since the COVID-19 pandemic came, we have found that facilities that use smart home system technology are urgently needed at this time, because during the pandemic, work and learning activities turn into online activities. This research shows that the effectiveness of smart home system technology can make work and study activities more effective.